Penggunaan Metode Role Playing untuk Meningkatkan Hasil Belajar Etika Publik - Tarmujianto Tarmujianto (SAP (Susunan Artikel Pendidikan), 2020)
This study aims at determining and analyzing the effect of role-playing learning methods on the learning outcomes of CPNS training participants in 2019 in the Public Ethics course. This study used explanatory research methods, while the type of research used was experimental research. The design used in this research was the Nonequivalent Control Group Design. This design closely similar to the pretest-posttest control group design, however, in this design the experimental group and the control group were not randomly selected. The results showed that the use of role-playing learning methods was considered effective enough to improve the learning outcomes of Public Ethics. While classes that used the conventional lecture learning method can be said to be less effective in improving learning outcomes for the Public Ethics training course. The use of role-playing learning methods had an effect of 47.8% on the learning outcomes of the Public Ethics training course, while the remaining 52.2% was influenced by factors other than the use of role-playing learning methods.